Adapted combat sports on bone related variables and functional independence of postmenopausal women in pharmacological treatment: a clinical trial study - Borba-Pinheiro, Claudio Joaquim; Martin Dantas, Estélio Henrique; de Souza Vale, Rodrigo Gomes; Drigo, Alexandre Janotta [UNESP]; de Alencar Carvalho, Mauro César Gurgel; Tonini, Teresa; Meza, Edgar Ismael Alarcon; de Figueiredo, Nébia Maria Almeida (Int Scientific Literature, Inc, 2016)
Background & study Aim: Osteoporosis is a chronic disease that leads to bone fragility and is associated with fracture risks and serious consequences for mobility. The aim of study was effects of adapted judo and karate programs of on bone mineral density (BMD), functional autonomy (FA), muscular strength and quality-of-life (QoL) of postmenopausal women in pharmacological treatment and low socioeconomic level. Material & Methods: To the clinical trial study, 50 volunteers distributed into three groups: adapted judo training (AJT, n = 17); adapted karate training (AKT, n = 17) and control group (CG, n = 16). The following assessment were used: bone mineral density by dual X-ray absorptiometry, `Latin America Group for maturity' protocol for FA, 10RM test for strength and `Osteoporosis Assessment Questionnaire' (OPAQ) for QoL. The adapted combat sports training were planned for 13 months with different intensities. ANOVA with Bonferroni post-hoc test were used. Results: Intra-groups (p<0.05) were observed in all BMD variables only AJT, besides of FA, leg strength and QoL for AJT and AKT. The AJT was significantly more efficient (p<0.05) compared with AKT, including: L-2-L-4 BMD (Delta% = 0.039%), total BMD (Delta% = 0.05%) and OPAQ (Delta% = 40.8%). In addition, both AJT and AKT were more efficient (p<0.05) compared with CG, including: FA (Delta% = 5.9%) and (Delta% = 4.7); Leg press at 45 (Delta% = 63.7%) and (Delta% = 53.7%); Knee extension (Delta% = 15.3%) and (Delta% = 14.5%), respectively. For OPAQ total only AJT presented better results (Delta% = 35.4%) compared with CG. Conclusions: The AJT presented favourable results for BMD and QoL, besides AJT and AKT showed better results for strength, FA and QoL compared to CG after 13 months. Therefore combat sport based on throws and grips of immobilisation of opponent's body (judo, sambo, wrestling etc.) they are likely to be optimal in achieving training effects measured in this work.
Keywords: Bone density; Functional autonomy; Muscle strength; Physical function; Quality of life